PENENTUAN TINGKAT KEBISINGAN SEPEDA MOTOR KNALPOT STANDAR DAN MODIFIKASI - Nasib '; Erwin '; Juandi M (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The noise level produced by standard and modified motorcycles exhaust has been investigated. In this research, there were three types of motorcycles used namely Honda, Suzuki and Yamaha. Noise levels that generated by those motorcycles were measured using Sound Level Meter (SLM) SL 4112. In order to eliminate noise from other sources 5 different  angles (0o, 45o, 90o, 135o, and 180o) were used, then the measurement of noise from the motorcycles exhaust was done 2m from the exhaust. The results of the measurement showed that sound intensity generated by  standard motorcycle exhaust at angle of 90o produced maximum value of 78,17 dB, 79,62 dB and 97,55 dB for Honda, Suzuki and Yamaha respectively. By modifiying the exhaust, the noise level produced of Honda, Suzuki and Yamaha were 97,48 dB, 97,62 dB and 97,55 dB respectively. The significant increase  of noise level for modified exhaust with muffler was caused by several factors such as muffler and diameter of exhaust. The range value of noise level for the standard exhaust was measured at the angle of 90oand the engine variation of 5000 rpm was 78,66 dB while for the modified exhaust produced an average value of 97,55 dB with the same position and engine variation.